Pembaharuan Hukum Keluarga Islam Kontemporer di Indonesia: Aturan Batas Usia Nikah oleh Lembaga Perkawinan dan Relevansinya dengan Hukum Islam - Rika Ramadhani; Lilik Andaryuni (CV. Creative Tugu Pena, 2024)
Law is a flexible thing, as is Islamic law. The provisions and rules contained in the law depend on developments over time and the conditions of society in the region. In Indonesia, the household life of Islamic families is regulated by the institution of marriage. One of the reforms in Islamic family law that occurred in Indonesia focused on the age limit regulations for marriage implemented by marriage institutions. This reform was implemented in an effort to deal with social change and as a preventive measure against early marriage, which often has a negative impact on family stability and individual well-being. The revised Indonesian marriage law contained in Law Number 16 of 2019 sets the marriage age limit for men and women at 19 years, and regulates the provisions for marriage dispensation for individuals under that age. From the perspective of Islamic law, this change is not considered contrary to religious teachings. Even though there are hadith arguments that allow marriage at an early age, the Qur'an prioritizes biological, psychological maturity and financial readiness as conditions for marriage. Government policy regarding the minimum age limit for marriage is seen as relevant to the principle of maslahah in Islam, which aims to protect and promote the welfare of society. The aim of this research is to identify the classical Islamic legal view regarding the marriage age limits set by the Indonesian government, as well as its relevance to the current social context.